Neem leaves (Azadirachta Indica) and Jasmine flowers (Jasminum sambac): A toxic combination of Aedes aegypti - Putri Ayu Irodah; Moh. Mirza Nuryady; N. Nurwidodo (Green and Tropical Laboratory for Sustainability, 2024)
Background: The high number of cases of dengue hemorrhagic fever (DHF) in Indonesia indicates the lack of diseases prevention caused by mosquito vectors. Chemical control efforts can cause resistance to mosquitoes, so it is necessary to have natural insecticides derived from plants, one of which is neem and jasmine which has active ingredients as larvicides. Objectives: This research aims to analyze the effect of different concentrations of extracts from neem (Azadirachta indica) and jasmine (Jasminum sambac) leaves on the mortality of Aedes aegypti larvae. Methods: This research is true experimental research using 7 treatments, there are negative control group using distilled water and a positive control group using 1% abate and 5 treatment groups using combination of extracts from neem leaves (Azadirachta indica) and jasmine flower (Jasminum sambac) with concentration ratio 0%:100%, 25%:75%, 50%:50%, 75%:25%, dan 100%:0%. In this study, it is used Aedes aegypti larvae taken by landing collection in Nguling, Pasuruan. Results: The results of identification of larvae showed that the larvae taken were Aedes aegypti larvae in terms of morphological characteristics. The results showed that the combination of 50%: 50% concentration caused a lot of mortality in larvae and obtained LC50 from the extract of neem (Azadirachta indica) and jasmine flower (Jasminum sambac) was 253,57 µg / mL. Conclusion: Extracts from neem leaves (Azadirachta indica) and jasmine flowers (Jasminum sambac) can be used as an candidate alternative to Aedes aegypti larvicide.